Imaging of human glioblastoma cells and their interactions with mesenchymal stem cells in the zebrafish (Danio rerio) embryonic brain - Vittori, Milos (Radiol Oncol, 2016)
BACKGROUND: An attractive approach in the study of human cancers is the use of transparent zebrafish (Danio rerio) embryos, which enable the visualization of cancer progression in a living animal. MATERIALS AND METHODS: We implanted mixtures of fluorescently labeled glioblastoma (GBM) cells and bonemarrow-derived mesenchymal stem cells (MSCs) into zebrafish embryos to study the cellular pathways of their invasion and the interactions between these cells in vivo. RESULTS: By developing and applying a carbocyanine-dye-compatible clearing protocol for observation of cells in deep tissues, we showed that U87 and U373 GBM cells rapidly aggregated into tumor masses in the ventricles and midbrain hemispheres of the zebrafish embryo brain, and invaded the central nervous system, often using the ventricular system and the central canal of the spinal cord. However, the GBM cells did not leave the central nervous system. With co-injection of differentially labeled cultured GBM cells and MSCs, the implanted cells formed mixed tumor masses in the brain. We observed tight associations between GBM cells and MSCs, and possible cell-fusion events. GBM cells and MSCs used similar invasion routes in the central nervous system. CONCLUSIONS: This simple model can be used to study the molecular pathways of cellular processes in GBM cell invasion, and their interactions with various types of stromal cells in double or triple cell co-cultures, to design anti-GBM cell therapies that use MSCs as vectors.